3D-printed polycaprolactone-chitosan based drug delivery implants for personalized administration. (February 2022) - Yang, Yutong; Wu, Haichao; Fu, Qiliang; Xie, Xinfeng; Song, Yongming; Xu, Min; Li, Jian
Graphical abstract: Highlights: Polycaprolactone and water-soluble chitosan were combined in 3D-printed drug delivery implant for sustained-release. All the materials of the 3D-printed implant are biocompatible, biodegradable, low-toxic, cost-effective, renewable, and the method is simple and green. The preparation process was carried out below 120 °C and solvent-free to maintain the drug activity. Sustained release reached 99% and lasted for 120 h by tailoring the drug and chitosan content of the 3D-printed implant. Abstract: Fused deposition molding (FDM) can complete most complex preparation of drug delivery implants to meet the personalized needs of patients. However, the drug activity has strict requirements on processing temperature and preparation method of filaments, the implant also has strict biocompatibility requirements for the materials. In this study, a drug delivery implant was prepared with good biocompatibility, controlled and efficient drug release using FDM printing for personalized administration. Drug-loaded filaments were developed for FDM process by hot-melt extrusion (HME). Polycaprolactone was used as a drug delivery carrier, and ibuprofen as the model drug. Notably, chitosan was dissolved to form controlled and efficient release channels. The printability, changes in physical and chemical properties during HME and FDM processes of the filament, and drug release behavior, mechanism and biocompatibility of the implants were investigated. The results showed that the filament tensile strength decreased with the increase of drug and chitosan content. No obvious degradation and chemical change occurred during the whole process. The drug release efficiency could reach>99% and lasted for 120 h mainly via the diffusion - erosion mechanism. The viability of cells cultured for 24 h in 72 h, 100% implant extract was 75.3%.